PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL LEARNING CYCLE 7E DI KELAS IV SDN RAWAJATI 03 PAGI - Riri Tohari Putri; Dudung Amir soleh; Gusti Yarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research applied the Learning Cycle 7E model as an effort to enhance mathematics learning in Grade IV-B of SDN Rawajati 03 Pagi. The study was conducted in the second semester of the 2025/2026 academic year with 31 students as participants. The research design followed the Kemmis and McTaggart model, which involves four stages: planning, implementation, observation, and reflection, carried out in two cycles. Data were collected through teacher and student activity observations, written tests to measure learning achievement, and documentation of classroom practices. The analysis revealed that in Cycle I, only 58% of students achieved mastery, with teacher activity at 77% and student activity at 72%. After improvements were made in Cycle II, student mastery increased to 84%, while teacher and student activities rose to 97% and 91%, respectively. These findings demonstrate that the Learning Cycle 7E not only improves mathematics learning outcomes but also fosters a more active, interactive, and meaningful classroom atmosphere. The model therefore holds strong potential as an alternative learning strategy to promote student participation, conceptual understanding, and positive learning experiences in elementary education.